Sertão se traz na alma? território/lugar, memória e representações sociais. - Mendes, Geisa Flores (2009)
This thesis analyses the movement of the senses present in the social memory about the outbacks. In this way, there has been an interpretative effort that used as reference the undertow outbacks denomination present in the documents that mention the process of occupation and housing in Bahia country and that includes, generically, an area of geographic transition between the coast line and the Caatinga ( a tract of land covered with crooked trees and prickly plants),structured around the present Vitória da Conquista city. The argument that permeates this study is that memory and representations are intrinsically linked to the process of socio spatial production. In this sense, it has aimed to a theoretic approximation between the concepts of territory, place, memory and social representations, exercising an interdisciplinar dialog, that maintains, however, the peculiarity of a geographic sense. Concerning to the geographic concepts, the theoretical support adopted based itself mainly on Carlos (1996), Castro (1992, 1997), Claval (1999, 2001), Corrêa (1994, 1997), Cosgrove (1998, 1999), Haesbaert (1997, 1999, 2002, 2004), Massey (2000, 2008), Moraes (2005a, 2005b), among others. As regard to memory, the theoretical anchor was based specially on Halbwachs (1990), Pollak (1989, 1992) e Fentress e Wickham (1992). Em Chartier (1990), Bourdieu (2007) e Jodelet (1991), was found the theoretical reference to comprehend the function of the elements that pervade the social representations and the strategies of mobilization that materialize itselves in the socio spacial production. In the specific discussion about outbacks, fundamental subsidies were given by Amado (1995), Almeida (2003, 2008), Arruda (2000), Bolle (2004), Lima (1999), Rodrigues (2001),among others. Concerning to the methodological procedures, different sources were used: application of questionnaires, realization of interviews, documental research in newspaper and local blogs. Memory as much as representations organizes itself and manifests in a multiplicity of languages. So, relating to the methodological aspects, the Discourse Analysis pointed elements that provided a better understanding of the productions of sense inherent to several types of discourses that per passed the research focus. As an initial proposition, it believed that when the places develop, get out off the isolation and precariousness of circulation route and the means of communication, the approximation with the idea of outbacks get in distance. However, the empiric work has showed that, even in a separating movement, simultaneously, there is a movement of permanence. It has been verified that life around outbacks are marked by ambivalences and by a plurality of look that constitute themselves by inclusion and exclusion socio spatial, material and immaterial bases, permanence and ruptures, spatiality and temporality that make possible to apprehend the conception of a back wood territory/place in the memory and in the social representations. Such ambivalences attest multiple outbacks marked by wefts and interlacing,considering what has been lived, noticed and conceived. It was still realized that, in the confluence of several discourses, exist different spaces of stabilization that, many times, put themselves in conflict, producing clivagens (land layers), recovering and insertions. The conceptions of outbacks are, therefore, constantly making itself, so the space is.